2020
DOI: 10.1016/j.eats.2020.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Anterolateral Ligament Reconstruction Using the Semitendinosus Tendon With Suspensory Tibial Fixation

Abstract: The anterolateral ligament (ALL) plays an important role in isolated anterior cruciate ligament reconstruction by providing rotational stability in a combined anterior cruciate ligament and anterolaterally injured knee. Although the ALL has been difficult to characterize anatomically, it originates near the lateral epicondyle of the distal femur and inserts into the proximal tibia between Gerdy's tubercle and the fibula head. Here, we describe an isometric ALL reconstruction using the semitendinosus tendon and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…ACL reconstruction can be divided into isometric ACL reconstruction and anatomical ACL reconstruction according to the positioning of the femoral tunnel. Kim et al (12) were of the view that positioning at isometric points helps to maintain the stability of the knee joint by keeping ACL in continuous tension during flexion and extension. As a classic technique of isometric reconstruction, the TT technique has a number of advantages, including that it is an easy operation to perform and its reproducibility is high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACL reconstruction can be divided into isometric ACL reconstruction and anatomical ACL reconstruction according to the positioning of the femoral tunnel. Kim et al (12) were of the view that positioning at isometric points helps to maintain the stability of the knee joint by keeping ACL in continuous tension during flexion and extension. As a classic technique of isometric reconstruction, the TT technique has a number of advantages, including that it is an easy operation to perform and its reproducibility is high.…”
Section: Discussionmentioning
confidence: 99%
“…By improving the traditional TT technique, the intraarticular orifices of the femoral tunnel can be located between the anteromedial bundle and the posterolateral bundle by turning the knee joint inward and rotating the knee joint inward during the creation of the femoral tunnel (12,24). After a follow-up period of more than 2 years, we found that the knee joint function scores and stability evaluations of the two groups were significantly improved compared with those before surgery, and there was no statistically significant difference between the two groups.…”
Section: B C Amentioning
confidence: 99%
“…Apart from GT, the ST has been also widely used for ALLR[ 46 ]. Kim et al [ 50 ] harvested the contralateral ST for ALLR, as the ipsilateral ST had been already used for ACLR during the same or previous procedure. The double-bundle graft was first attached on the tibia (midway between the fibular head and Gerdy’s tubercle) using an adjustable length loop button, then passed deep to ITB and finally fixed posterior and proximal to the lateral femoral epicondyle with an interference screw, while the knee was positioned in 30º of flexion and neutral rotation.…”
Section: Autograftsmentioning
confidence: 99%
“…The type of ALLR procedure affects knee kinematics and stability. 28 Autograft options for ALLR are the semitendinosus, 23 gracilis, 4 peroneus longus, 9 and plantaris 22 tendons. The use of allografts and synthetic grafts has also been described.…”
mentioning
confidence: 99%